The metabolites of gut microbiota: their role in ferroptosis in inflammatory bowel disease - Jingying Zhou; Penghui Lu; Haolong He; Ruhan Zhang; Dican Yang; Qiong Liu; Qianyan Liu; Mi Liu; Guoshan Zhang (European Journal of Medical Research)
Abstract Inflammatory bowel disease (IBD) includes chronic inflammatory conditions, such as Crohn's disease and ulcerative colitis, characterized by impaired function of the intestinal mucosal epithelial barrier. In recent years, ferroptosis, a novel form of cell death, has been confirmed to be involved in the pathological process of IBD and is related to various pathological changes, such as oxidative stress and inflammation. Recent studies have further revealed the complex interactions between the microbiome and ferroptosis, indicating that ferroptosis is an important target for the regulation of IBD by the gut microbiota and its metabolites. This article reviews the significant roles of gut microbial metabolites, such as short-chain fatty acids, tryptophan, and bile acids, in ferroptosis in IBD. These metabolites participate in the regulation of ferroptosis by influencing the intestinal microenvironment, modulating immune responses, and altering oxidative stress levels, thereby exerting an impact on the pathological development of IBD. Treatments based on the gut microbiota for IBD are gradually becoming a research hotspot. Finally, we discuss the potential of current therapeutic approaches, including antibiotics, probiotics, prebiotics, and fecal microbiota transplantation, in modulating the gut microbiota, affecting ferroptosis, and improving IBD symptoms. With a deeper understanding of the interaction mechanisms between the gut microbiota and ferroptosis, it is expected that more precise and effective treatment strategies for IBD will be developed in the future.